Empowering the Community to Design a Household Waste Management System Through Design Thinking - Suryadi, Ronald Julion; Octavia, Johanna Renny (RSF Conference Series: Business, Management and Social Sciences, 2022)
The waste issue caused by a linear economy concept has a serious impact on the environment, society, and economy. The damage of this issue is threatening the community’s resilience and well-being today and in the future. For instance, Bandung City had suffered a waste disaster in 2005 which is known as Bandung Lautan Sampah. In line with this, the local government of Bandung City has implemented the Reduce, Separate, and Benefit (KangPisMan) program which targets each region to reduce waste by 30% by 2025. Overall, the waste generation data indicated that Bandung City will not achieve the reduction target. To mitigate the worst scenario, it is necessary to accelerate the adoption of a suitable waste management system in the city, especially in the household area where the majority of waste comes from. Thus, the objective of this research was to design a pilot project that empowers a community to reduce household waste. The community involved in this pilot project for the design of a household waste management system was the residents of RW 005, Cisaranten Kulon Village, Bandung City. Design thinking was applied as the research methodological approach, given that waste is a complex, wicked problem. Through design thinking, we expect to design a waste management system, that is human-centered and sustainable, as a solution to this problem. In this research, together with the community, we have successfully developed a system prototype, which consists of a waste material flow system, an organization structure, a circular business model canvas (CBMC), a Standard Operating Procedure (SOP) for waste transportation, and a door-to-door education program. Furthermore, the prototypes will be implemented and evaluated for prototype improvement.